Maintaining High-Quality Multidisciplinary Pain Medicine Fellowship Programs: Part I: Innovations in Pain Fellows' Education, Research, Applicant Selection Process, Wellness, and ACGME Implementation During the COVID-19 Pandemic. Issue 8 (29th April 2020) - Kohan, Lynn; Moeschler, Susan; Spektor, Boris; Przkora, Rene; Sobey, Christopher; Brancolini, Scott; Wahezi, Sayed; Anitescu, Magdalena
Abstract: Background: Pain fellowship programs are facing unique challenges during the COVID-19 pandemic. Restrictions from state governments and the Centers for Disease Control and Prevention have resulted in a rapidly changing and evolving learning environment for todays' fellows. Innovative solutions must be sought to guarantee that proper education is maintained and to ensure the well-being of our trainees. Methods: We assembled a panel of pain program directors who serve as officers/board members of the Association of Pain Program Directors to provide guidance and formulate recommendations to pain fellowship directors nationally. This guidance is based on reviewing current changes to the Accreditation Council for Graduate Medical Education (ACGME) and American Board of Anesthesiology policies and best available evidence and expert opinion on the use of remote educational activities, research endeavors, and trainee wellness. Conclusions: The country is in the midst of an unprecedented pandemic. The impact on pain management fellowships has been severe and will likely last for months, resulting in extraordinary challenges to the administration of pain fellowship programs and the education of our fellows. Understanding revisions to ACGME policies, using technology to promote remote learning opportunities, and providing trainees with opportunities to alleviate their anxiety and encourage mental health are beneficial strategies to implement. Together, we can implement innovative solutions to help overcome these challenges.